Deep Placement of Briquette Urea Increases Agronomic and Economic Efficiency of Maize in Sandy Loam Soil - Krishna Dhakal; Bandhu Raj Baral; Keshab Raj Pokhrel; Naba Raj Pandit; Surya Bahadur Thapa; Yam Kanta Gaihre; Shree Prasad Vista (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Imbalanced use of fertilizers along with inappropriate sources and application methods has attributed to reduced nitrogen use efficiency (NUE) and crop productivity. The use of the right N source and appropriate application method is essential to reduce N losses and increase NUE, crop yield, and economic return. A field trial was conducted at the Agricultural Research Station, Dasharathpur, Surkhet following a randomized complete block design with seven treatments (three replications) using various N sources (urea, urea briquette, and three different blended fertilizers) and their application methods to assess their fertilizing efficiencies. Treatments showed a significant effect (p<0.05) for all the traits viz. plant and ear height, stover and grain yield, harvest index, and thousand-grain weight. Compared to the recommended dose of fertilizer (RDF), the grain yield advantage of blended fertilizer (10:26:26 NPK) in a combination of Zinc followed by RDF+Zn and urea deep placement (UDP) applied treatments were 7.8, 2.7, and 2.4% respectively. Among all, deep placement of urea briquette was found to be economic for the cultivation of Khumal Hybrid-2 maize variety while producing similar yield (2.4% higher) with 25% lower nitrogen dose, increasing agronomic nitrogen use efficiency by 10.41 kg/kg N, and economic benefit by US30.4/ha compared to RDF.